2013
DOI: 10.3748/wjg.v19.i3.355
|View full text |Cite
|
Sign up to set email alerts
|

Biliary fistula after treatment for hydatid disease of the liver: When to intervene

Abstract: Patients with PBF after hydatid surgery often have complicated postoperative course with serious morbidity. Patients who develop PBF with an output < 102 mL might be managed expectantly.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
1
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(29 citation statements)
references
References 24 publications
0
26
1
1
Order By: Relevance
“…[11][12][13] In this study most of the patients with hydatid disease of the liver presented with vague abdominal pain and dyspeptic symptoms but many of them were asymptomatic as reported in other studies. 8,14 In the current study, the main diagnostic modalities employed were ultrasound and CT scan in all cases with diagnostic accuracy of 100%.This is comparable to 96% and 100% reported in different studies.…”
Section: Discussionmentioning
confidence: 77%
“…[11][12][13] In this study most of the patients with hydatid disease of the liver presented with vague abdominal pain and dyspeptic symptoms but many of them were asymptomatic as reported in other studies. 8,14 In the current study, the main diagnostic modalities employed were ultrasound and CT scan in all cases with diagnostic accuracy of 100%.This is comparable to 96% and 100% reported in different studies.…”
Section: Discussionmentioning
confidence: 77%
“…Of the 190 patients, 155 patients had only one cyst. Thirty-five patients had multiple (range, [2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20]. The sizes of the cysts were in the range of 20-170 mm (mean, 75 mm).…”
Section: Resultsmentioning
confidence: 99%
“…The aim of all treatment modalities for HLD should be to relieve symptoms, inactivate and completely remove viable scolices and germinative membranes, and manage the residual cavity. There is no best treatment option; various methods are available and include: medical therapy with benzimidazole compounds; conservative or radical surgery; percutaneous treatment; and a ''watch and wait'' approach (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)21,22). The success rate of medical therapy alone for HLD is 18-50%, with a recurrence rate of 3-30% (11)(12)(13)21).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Literature on this subject with regard to children is scarce (28). It was demonstrated that a postoperative biliary drainage volume <102 ml to be the only predictor of spontaneous closure of biliary fistula following liver HD surgery (31). Nevertheless, once conservative measures to control the post-surgical biliary leakage in children with huge liver hydatid disease are inadequate, the clinician dealing with these children should not hesitate to perform ERCP and sphincterotomy.…”
Section: Discussionmentioning
confidence: 99%